Mineral component of mineralizations in different types of breast lesions and their correlation with diseases - Chang-qiu Wang; Xiao Cheng; Xiao Ge; Hong-rui Ding; Yan Li; An-huai Lu (China Geology)
ABSTRACT: Pathological mineralizations in breast lesions are closely associated with disease progression and serves as a critical diagnostic indicator. However, systematic understanding remains lacking regarding the phase categories, distribution patterns, and proportional occurrences of mineral phases across different breast lesion types. The diagnostic implications of specific phases, such as calcium oxalate, for distinguishing benign and malignant lesions remain controversial. This study employed polarizing microscopy, environmental scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy to analyze the phase composition of 61 mineralized samples from three lesion types: Invasive carcinoma, carcinoma in situ and benign lesions. Results demonstrate that breast lesion mineralizations predominantly comprise calcium phosphates, including hydroxyapatite (HA), amorphous calcium phosphate (ACP), and whitlockite, occasionally accompanied by calcium oxalate (monohydrate or dihydrate). Distinct distribution patterns and proportional occurrences of minerals were observed among the three types of lesion mineralizations. HA, as the predominant phase, was ubiquitously present across all three lesion categories. ACP, a mineralization precursor phase, emerged during early mineralization stages across all lesion types. Notably, whitlockite exclusively occurred in benign lesions and carcinoma in situ, with higher prevalence in benign cases, suggesting a progressive decline in Mg2+ concentration within the lesion microenvironment as malignancy advances. Calcium oxalate coexisted with HA in mineralized regions across all lesion types, and its presence in invasive carcinoma specimens warrants heightened clinical attention.